Plant-based sterols and stanols in health & disease: "Consequences of human development in a plant-based environment?". (April 2019) - Plat, J.; Baumgartner, S.; Vanmierlo, T.; Lütjohann, D.; Calkins, K.L.; Burrin, D.G.; Guthrie, G.; Thijs, C.; Te Velde, A.A.; Vreugdenhil, A.C.E.; Sverdlov, R.; Garssen, J.; et al.
Abstract: Dietary plant sterols and stanols as present in our diet and in functional foods are well-known for their inhibitory effects on intestinal cholesterol absorption, which translates into lower low-density lipoprotein cholesterol concentrations. However, emerging evidence suggests that plant sterols and stanols have numerous additional health effects, which are largely unnoticed in the current scientific literature. Therefore, in this review we pose the intriguing question "What would have occurred if plant sterols and stanols had been discovered and embraced by disciplines such as immunology, hepatology, pulmonology or gastroenterology before being positioned as cholesterol-lowering molecules?" What would then have been the main benefits and fields of application of plant sterols and stanols today? We here discuss potential effects ranging from its presence and function intrauterine and in breast milk towards a potential role in the development of non-alcoholic steatohepatitis (NASH), cardiovascular disease (CVD), inflammatory bowel diseases (IBD) and allergic asthma. Interestingly, effects clearly depend on the route of entrance as observed in intestinal-failure associated liver disease (IFALD) during parenteral nutrition regimens. It is only until recently that effects beyond lowering of cholesterol concentrations are being explored systematically. Thus, there is a clear need to understand the full health effects of plant sterols and stanols. Highlights: Dietary plant sterols and stanols lower low density lipoprotein cholesterol, a causal risk factor for cardiovascular diseases Although plant sterols and stanols are poorly absorbed they are taken up by various organs, which may affect health and disease. Plant sterols and stanols may play a crucial role in functioning of immune cells and have beneficial effects beyond lowering low density lipoprotein cholesterol Effects of plant sterols on liver health depend on the route of administration as observed during parenteral nutrition regimens Intracellular oxidation of plant sterols might be a protective response avoiding accumulation of plant sterols within the cell.